NEUROMUSCULAR TAPING IMPROVES MICROVASCULAR CIRCULATION IN TYPE 2 DIABETES MELLITUS PATIENTS - Andriani, Rizki; Qaribi, Mahanta; Putri, Roofi Asma; Fadhillah, Arif; Helmi, Sabrina; Septiani, Delia (Nurse and Health: Jurnal Keperawatan, 2024)
Background: The most common complications in Diabetes Mellitus patients are foot problems and high risk for amputation. Factors that trigger problems in diabetic feet in the form of neuropathy factors, namely loss of sensory nerve function and circulatory disorders. One of the non-pharmacological therapies to prevent these problems is safe Neuromuscular Taping (NMT) which is applied to the skin with elastic plaster through a decompression method to prevent a decrease in peripheral blood circulation and improve blood circulation. Objectives: The purpose of this study was to determine the comparison of the effectiveness of Neuromuscular Taping (NMT) intervention on microvascular circulation which was assessed by Ankle Brachial Pressure Index (ABPI) measurement in type 2 Diabetes Mellitus patients. Methods: This study used a quasi-experimental research design with a pretest-posttest control group approach. The number of respondents to this study was 60 type 2 DM patients divided into treatment group respondents and control group respondents. The intervention group was given NMT intervention for 2 weeks with daily plaster changes while the control group was given standard foot care education. The data collected is an ABPI score that describes microvascular circulation using a sphygmomanometer. Analysis was carried out using paired sample t-tests which were used to determine the effectiveness of the intervention. Results: Based on the results of the study, significant changes were obtained in the microvascular circulation of the treatment group (p = 0.000) α 0.05 which is the category of normal microvascular circulation or no disturbance. Increased microvascular circulation is caused by the application of NMT for 2 weeks. Conclusion: There was an increase in microvascular circulation seen through changes in Ankle Brachial Pressure Index (ABPI) values before and after Neuromuscular Taping (NMT) intervention. There were significant differences between the intervention and control groups in changes in ABPI scores.